Uma tradição indesejada: o desejo de uniformização na Grande Reforma Urbana do Rio de Janeiro (1903-1906) como condição da civilização e do progresso em terras cariocas (Revista de História Regional, 2025)
The article in question deals with a specific aspect of the Great Urban Reform of Rio de Janeiro, which took place between 1903 and 1906: it reflects on a common aspect of municipal urban reform and its federal counterpart, namely: the desire to standardize behavior of the Rio population, which they perceived as an indispensable element of what they believed to be a process of realizing "civilization" and "progress" in Rio de Janeiro lands. This movement of both reforming bodies ignored the presence of a secular tradition - in the sense given by H. G. Gadamer - of uses of the urban space of the city of Rio.
Keywords: reforma urabana; progreso